Academic Procrastination and Learning Outcome of Undergraduate Students Studying at Gangadhar Meher University - Baral, Rajashree; Kumbhakar, Barun; Meher, Venkateswar (International Journal of Psychosocial Rehabilitation, 2020)
The present study investigates the academic procrastination and learning outcome of undergraduate learners studying at Gangadhar Meher University. For the study, both casual comparative and correlational research methods were employed to accomplish the objectives. The present research aims at examining the academic procrastination and learning outcome of undergraduate students and studying the relationship between academic procrastination and learning outcome concerning streams i.e. Arts, Science, Commerce, and sex i.e. boys and girls. For the present study, a total number of 210 undergraduate students from GM University Sambalpur were selected as the sample through stratified random sampling considering streams and sex as the strata, from each stream, 70 students were taken where 35 were boys and 35 were girls. To collect data, the academic procrastination scale developed by Justin McCloskey and Shannon A. Scielzo (2015) was administered and the learning outcome scores of the selected students were collected. For comparison purposes, the investigators applied the ‘t’ test and Pearson’s coefficient of correlation for studying relationship purpose, and the statistical significance was tested at 0.05 and 0.01 level. The findings of the study revealed a significant difference between the achievement scores of students having high and low academic procrastination scores, which revealed that the students having less academic procrastination scores were having more learning outcome scores. The results of the study also revealed a significant negative relationship between the academic procrastination scores and learning outcome scores of undergraduate students concerning their sex and stream, which revealed that the learning outcome of students increases with the decrease of academic procrastination scores.